In silico prediction of Ames mutagenicity for organosilicon compounds: Exploring and enhancing chemical space boundaries - Barbara G. Schmitt; Emilio Benfenati; Robert S. Foster; Grace Kocks; Giuseppa Raitano; Rachael E. Tennant; Carole Forlini; Eckart Gura; Shawn Seidel; Farah Koraichi-Emeriau (Regulatory Toxicology and Pharmacology, 2026)

West Antarctic subglacial geology distinguished by Pb isotopes and Rb–Sr ages in ice-rafted feldspars - Thomas Arney; Claus-Dieter Hillenbrand; Thomas M. Belgrano; J. Andy Milton; Christine S. Siddoway; Gavin L. Foster; Paul A. Wilson; Julia S. Wellner; Steve M. Bohaty (Earth and Planetary Science Letters, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

A quantitative comparison of tools for monitoring the abundance of crown-of-thorns starfish and coral cover - Emma Lawrence; Scott D. Foster; Samuel A. Matthews; David Williamson; Morgan S. Pratchett; Jason Doyle; Scott Bainbridge; Sven Uthicke; Peter C. Doll; Brano Kusy; Mohammad A. Armin; Mary C. Bonin (Coral Reefs, 2026)
Effective monitoring of crown-of-thorns starfish (COTS) populations and coral cover is critical for informing management of COTS outbreaks throughout their tropical Indo-Pacific range, including Australia’s Great Barrier Reef. However, existing monitoring tools such as manta tow and cull diver surveys have well-known limitations including accuracy and resource demands. This study evaluates a range of monitoring tools for assessing both COTS and coral populations. Tools that measure both COTS and coral include manta tow surveys, scooter-assisted large area diver-based (SALAD) surveys and surveys undertaken using the ReefScan towed camera platform. For COTS-only monitoring, we examine cull diver surveys and environmental DNA (eDNA) sampling. Data from side-by-side deployments on seven to ten reefs (depending on the tool) with varying COTS densities and coral cover were collected and analysed to calibrate estimates between tools. The calibration models developed will aid in integrating data from diverse sources and facilitate the translation of estimates based on one monitoring tool to another. Critically, the models provide a means of estimating COTS density (COTS per hectare) for monitoring tools that do not directly collect this measure, allowing more meaningful decision-making around ecological thresholds and enabling threshold-based management regardless of which tool collected the data. The study emphasises that each tool has specific applications for addressing knowledge gaps and informing management decisions, advocating for an integrated, multi-tool monitoring strategy that leverages the strengths of each tool to improve the overall effectiveness and efficiency of COTS and coral monitoring.

An interactive tool to identify existing evidence and research gaps on agricultural production processes to address heavy metals in foods: developed from a scoping review - Rupal Trivedi; Lauren E. O’Connor; Cassi N. Leta; Trish J. Bosse; Julie S. Davis; Arin A. Balalian; Rachel C. Thoerig; Shailesh M. Advani; Margaret J. Foster; Kyle M. Holland; David D. Baltensperger; Delbert M. Gatlin III; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Sequestration of chlorine in scapolite during metamorphism and the formation and role of residual bittern brines for mineralized systems in the Mesoproterozoic Belt Supergroup, North America - I.M.T. Rein; J. Hammerli; R.S. Lewis; M. Foster; S. Boroughs (Chemical Geology, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Novel Insights into Mechanisms of Pain Caused by Radiotherapy - Jeffrey A. Foster; Sun H. Park; Joseph Moore; Kaitlyn E. Reno; Alicia Costa-Terryll; Leslie Kim; Michael T. Munley; Jeffrey S. Willey (Current Stem Cell Reports, 2026)
Purpose of Review Radiotherapy serves as a palliative option for alleviating cancer pain but can also elicit chest wall pain following stereotactic body radiotherapy (SBRT). The etiology of chest wall pain remains unclear but may relate to SBRT effects on normal ribs and responses from activated osteoclasts. This review explores potential mechanisms and treatment strategies for this increasingly common complication for patients undergoing radiotherapy. Recent Findings Radiation-induced bone loss is likely multifactorial, involving changes to bone microvasculature, suppressed angiogenesis, osteoblast damage and senescence, as well as increased resorption via activated osteoclasts. Preliminary data suggest that inhibiting osteoclasts may prevent radiation-induced chest wall pain and rib fracture. Our laboratory has identified TGF-βR1 as a potential central mediator of radiation-induced bone loss and pain signaling between osteoclasts and sensory neurons. Summary Advances in radiotherapy have optimized tumor targeting and control. However, radiation-induced musculoskeletal toxicity remains prevalent. Recent findings suggest targeted inhibition of TGF-β signaling between osteoclasts and neurons may offer a therapeutic strategy to mitigate radiation-induced pain.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Formulation and evaluation of probucol-LCA nanoparticles for supressing oxidative stress-related retinal degeneration - Susbin Raj Wagle; Alicia Brunet; Rebekah James; Le Yang Sen; Mikhaela Manuel Lorenzo; Bozica Kovacevic; Mengistie Diress; Thomas Foster; Corina Mihaela Ionescu; Patrick Lim; Livia S. Carvalho; Armin Mooranian; et al. (Drug Delivery and Translational Research, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Estrogen-containing contraceptive use and blood lead concentrations in a cohort of premenopausal individuals - Lauren E. Chapman; Mandy S. Hall; Arianna Foster; Donna D. Baird; Quaker E. Harmon; Robert O. Wright; Julio A. Landero; Renee Heffron; Lauren A. Wise; Ganesa Wegienka; Ruth J. Geller; Amelia K. Wesselink; et al. (Environmental Research, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

Parental Weaning Style Intent vs Reality: What Factors Affect If a Parent Intends and Completes Baby-led Weaning, Mixed Weaning, or Traditional Weaning - K. Whitley; D. Jacobvitz; S. Foster; L. Hernandez; M. Burgermaster; S. Dube; M. Abrego; A. Ramos-Gonzalez; M. Bradley; K. Ornelas; L. Sandoval-Mejia; I. Martinez; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Nutrient production, water consumption, and stresses of large-scale versus small-scale agriculture: A global comparative analysis based on a gridded crop model - Han Su; Timothy Foster; Rick J. Hogeboom; Diana V. Luna-Gonzalez; Oleksandr Mialyk; Bárbara Willaarts; Yafei Wang; Maarten S. Krol (Global Food Security, 2025)

Coverage matters: identifying and mitigating sampling frame issues in recreational fishing surveys - S. M. Taylor; A. de Groote; K. Hyder; J. H. Vølstad; B. W. Hartill; J. Foster; R. Andrews; K. L. Ryan (Reviews in Fish Biology and Fisheries, 2025)
Surveys play an integral part in monitoring and maintaining sustainable recreational fisheries. For any probabilistic survey, the selection of a sampling frame (e.g., list of individuals or fishers) is an important decision because it influences the ability to provide unbiased estimates of recreational catch and effort. Undercoverage occurs when units of the target population (i.e., the population of interest) are missing from the frame population. This error can undermine the reliability of research advice generated from survey estimates. In this review, we: (i) define six sampling frame configurations that are commonly applied in probabilistic recreational fishing surveys; (ii) synthesise how coverage errors associated with each configuration have been addressed for marine recreational fisheries globally; (iii) outline approaches to identify and correct for coverage errors; and (iv) recommend how to future-proof coverage issues. In our six case studies, multiple types of undercoverage were identified and addressed to varying extents, depending on the characteristics of each fishery and type of sampling frame used. Generalised list frames (particularly phone lists) are arguably the most prone to undercoverage error. To assist in future-proofing surveys, we recommend: (1) considering coverage error during survey planning; (2) designing pilot surveys or scheduling concurrent surveys to evaluate and/or correct for potential bias; (3) recognising that coverage error often changes through time; (4) using technological or multi-frame approaches to mitigate coverage error; (5) considering model-based survey tools to correct for undercoverage; and (6) documenting the sampling frame and potential sources of coverage error in publications. These recommendations extend to inland recreational fisheries, commercial fishing surveys and fisheries-independent surveys. Graphical abstract

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

Major global ports alter light regimes for marine biofouling communities - Nina Schaefer; Melanie J. Bishop; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D.H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Journal of Environmental Management, 2025)

Re-examination of archived materials reveals infection of zebra mussels Dreissena polymorpha in UK waters with the parasite Haplosporidium raabei - Rachel Foster; Jasmine E. Hunt; Kelly S. Bateman; Matthew J. Green; William Ball; Matt Longshaw; Laura Heath; Paul Stebbing; Georgia M. Ward (Biological Invasions, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

A call for strategic assessments of regional applications of solar radiation management: Exploring the challenges and opportunities from marine cloud brightening and albedo surface modification - U. Baresi; C.M. Baum; T.B. Fischer; S. Lockie; A. Piggott-McKellar; V. Graham; E. Bohensky; L.B. Fritz; N. Shumway; D.P. Harrison; R. Foster; B.K. Sovacool; et al. (Environmental Impact Assessment Review, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Integrated pest management enhances biological control in a US midwestern agroecosystem by conserving predators and non-pest prey - Ivan Grijalva; Amanda R. Skidmore; Marc A. Milne; Paola Olaya-Arenas; Ian Kaplan; Rick E. Foster; John S. Yaninek (Agriculture, Ecosystems & Environment, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Influence of habitat features on the colonisation of native and non-indigenous species - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Cian Foster-Thorpe; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Shinichi Nakagawa; Craig D.H. Sherman; Maria L. Vozzo; Katherine A. Dafforn (Marine Environmental Research, 2024)

Fine mapping of major QTL qshgd1 for spontaneous haploid genome doubling in maize (Zea mays L.) - Tyler L. Foster; Monika Kloiber-Maitz; Laurine Gilles; Ursula K. Frei; Sarah Pfeffer; Yu-Ru Chen; Somak Dutta; Arun S. Seetharam; Matthew B. Hufford; Thomas Lübberstedt (Theoretical and Applied Genetics, 2024)

Correction: Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh‑Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Just keep swimming? Observations of resting behavior in gray reef sharks Carcharhinus amblyrhynchos (Bleeker, 1856) - Robert W. Bullock; Craig Foster; James S. E. Lea (Journal of Fish Biology, 2024)
Understanding the respiratory modes of sharks has important implications for studying the metabolism, energetics, and behavioral strategies of different species. Here we provide the first reported observations of resting behavior in the gray reef shark Carcharhinus amblyrhynchos , a species typically considered an obligate ram ventilator. Observations were made at several locations in the Republic of Seychelles, where sharks were found resting under reef ledges and were unresponsive to the presence of divers. These findings update our understanding of the respiratory mode of this species and have implications for future research.

Variable effects of substrate colour and microtexture on sessile marine taxa in Australian estuaries - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D. H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Biofouling, 2024)

A model to assess the environmental and economic impacts of municipal waste management in Europe - P.F. Albizzati; G. Foster; P. Gaudillat; S. Manfredi; D. Tonini (Waste Management, 2024)

Threats to the persistence of sugar pine (Pinus lambertiana) in the western USA - Daniel E. Foster; Scott S. Stephens; Perry de Valpine; John J. Battles (Forest Ecology and Management, 2024)

Identifying opportunities for collective action around community nutrition programming through participatory systems science - Perla Chebli; Lan N. Đoàn; Rachel L. Thompson; Matthew Chin; Nasim Sabounchi; Victoria Foster; Terry T. K. Huang; Chau Trinh-Shevrin; Simona C. Kwon; Stella S. Yi (Cancer Causes & Control, 2023)

Modelled microgravity impacts Vibrio fischeri population structure in a mutualistic association with an animal host - Clotilde Bongrand; Jamie S. Foster (Environmental Microbiology, 2023)
Perturbations to host–microbe interactions, such as environmental stress, can alter and disrupt homeostasis. In this study, we examined the effects of a stressor, simulated microgravity, on beneficial bacteria behaviours when colonising their host. We studied the bacterium Vibrio fischeri, which establishes a mutualistic association in a symbiosis‐specific organ within the bobtail squid, Euprymna scolopes . To elucidate how animal–microbe interactions are affected by the stress of microgravity, squid were inoculated with different bacterial strains exhibiting either a dominant‐ or sharing‐colonisation behaviour in High Aspect Ratio Vessels, which simulate the low‐shear environment of microgravity. The colonisation behaviours of the sharing and dominant strains under modelled microgravity conditions were determined by counting light‐organ homogenate of squids as well as confocal microscopy to assess the partitioning of different strains within the light organ. The results indicated that although the colonisation behaviours of the strains did not change, the population levels of the sharing strains were at lower relative abundance in single‐colonised animals exposed to modelled microgravity compared to unit gravity; in addition, there were shifts in the relative abundance of strains in co‐colonised squids. Together these results suggest that the initiation of beneficial interactions between microbes and animals can be altered by environmental stress, such as simulated microgravity.

Assessing the utility of common arguments used in expert review of in silico predictions as part of ICH M7 assessments - Alex N. Cayley; Robert S. Foster; Alessandro Brigo; Wolfgang Muster; Alyssa Musso; Michelle O. Kenyon; Patricia Parris; Angela T. White; Mirit Cohen-Ohana; Raphael Nudelman; Susanne Glowienke (Regulatory Toxicology and Pharmacology, 2023)

A Comparison of Infant Diet Quality Indices in Infants 7-12 Months Old - S. Foster; D. Jacobvitz; L. Hernandez; H. Jones; M. Abrego; E. Widen (Journal of the Academy of Nutrition and Dietetics, 2023)

P25-14: Hepatic safety assessment of covalent inhibitor drug candidates - S. Amberntsson; B. Chouhan; A. Foster; G. Smith; S. Wilkinson; S. Harlfinger; S. Kavanagh; D. Williams (Toxicology Letters, 2023)

Trophic Niche Metrics Reveal Long-Term Shift in Florida Bay Food Webs - Stacy Calhoun-Grosch; Emelie M. Foster; W. Ryan James; Rolando O. Santos; Jennifer S. Rehage; James A. Nelson (Ecosystems, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Hydrodynamics and Sediment-Transport Pathways along a Mixed-Energy Spit-Inlet System: A Modeling Study at Chincoteague Inlet (Virginia, USA) - Ioannis Y. Georgiou; Francesca Messina; Md Mohiuddin Sakib; Shan Zou; Madeline Foster-Martinez; Martijn Bregman; Christopher J. Hein; Michael S. Fenster; Justin L. Shawler; Kaitlyn McPherran; Arthur C. Trembanis (Journal of Marine Science and Engineering, 2023)
Tidal-inlet systems are dynamic features that respond to short-term (e.g., storms) and longer-term processes (e.g., sea-level rise, changes in tidal prism). The Chincoteague Inlet system, located along the northern Eastern Shore of Virginia (USA), is a dynamic coastal complex that experiences rapid change associated with sediment redistribution and a shifting inlet throat due to the southern elongation of adjacent Assateague Island. In this study, a numerical model based on Delft3D with coupled flow–waves, multiclass sediment transport, and morphologic feedback was developed to quantify the hydrodynamic and geomorphic controls within this rapidly evolving inlet–spit system and to develop a more comprehensive understanding of regional to local controls on sediment-transport pathways. Model results show that most of the sand transport along southern Assateague Island is sequestered nearshore and proximally in deeper sinks within Fishing Point, and, of that, only finer sand sizes are transported around the spit, confirming previous analysis and hypothesis. The model also showed that sand transport toward the south increases along Wallops Island and quantified spatially explicit transport trends for selected sediment classes, revealing that coarser sediment bypassing is a punctuated process that is proportional to storms.

Complete genome sequence of zoysia mosaic virus, a novel member of the genus Poacevirus - Bishwo N. Adhikari; Jing Zhou; Xiaojun Hu; Roy S. Turner; Clint McFarland; Joseph A. Foster (Archives of Virology, 2023)

The interplay between Cs and K in Pseudanabaena catenata; from microbial bloom control strategies to bioremediation options for radioactive waters - Kejing Zhang; Lynn Foster; Dawn Buchanan; Victoria S. Coker; Jon K. Pittman; Jonathan R. Lloyd (Journal of Hazardous Materials, 2023)

Vector species, pasture legume host range, and impact on grain legumes of an Australian soybean dwarf virus isolate - B. S. Congdon; J. R. Baulch; K. J. Foster (Archives of Virology, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Introduction to the special issue in honor of the contributions of Lynn Margulis (1938–2011) Lynn Margulis: a 20th -Century scientist and a visionary of biology - Jamie S. Foster; Margaret J. McFall-Ngai (Symbiosis, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Plant performance responds to intraspecific variation in soil inocula from individual Solidago clones - Bryan S. Foster; Brendan B. Haile; Justin T. Campnell; Thomas Canam; Marci J. Gallagher; Scott J. Meiners (Plant Ecology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genomic characterization of silvergrass cryptic virus 1, a novel partitivirus infecting Miscanthus sinensis - Larissa C. Costa; Xiaojun Hu; Martha Malapi-Wight; Mary O’Connell; Leticia M. Hendrickson; Roy S. Turner; Clint McFarland; Joseph Foster; Oscar P. Hurtado-Gonzales (Archives of Virology, 2022)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Genetic structure and population history in two critically endangered Kaua‘i honeycreepers - Loren Cassin-Sackett; Michael G. Campana; Nancy Rotzel McInerney; Haw Chuan Lim; Natalia A. S. Przelomska; Bryce Masuda; R. Terry Chesser; Eben H. Paxton; Jeffrey T. Foster; Lisa H. Crampton; Robert C. Fleischer (Conservation Genetics, 2021)

Eosinophils and COVID-19: diagnosis, prognosis, and vaccination strategies - Helene F. Rosenberg; Paul S. Foster (Seminars in Immunopathology, 2021)

Cerebellar Grey Matter Volume in Older Persons Is Associated with Worse Cognitive Functioning - A. Buhrmann; A. M. A. Brands; J. van der Grond; C. Schilder; R. C. van der Mast; N. Rius Ottenheim; J. C. Foster-Dingley; A. S. Bertens; E. van den Berg (The Cerebellum, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Contribution of NDM and OXA-type carbapenemases to carbapenem resistance in clinical Acinetobacter baumannii from Nigeria - David O. Ogbolu; Oyebode A. Terry Alli; Adeolu S. Oluremi; Y. Temilola Ogunjimi; D. Iyanu Ojebode; Veronica Dada; Olubunmi O. Alaka; Ebenezer Foster-Nyarko; Mark A. Webber (Infectious Diseases, 2020)

Emergence of an evolutionary innovation: Gene expression differences associated with the transition between oviparity and viviparity - Charles S. P. Foster; Michael B. Thompson; James U. Van Dyke; Matthew C. Brandley; Camilla M. Whittington (Molecular Ecology, 2020)
Our understanding of the evolution of complex biological traits is greatly advanced by examining taxa with intermediate phenotypes. The transition from oviparity (egg‐laying) to viviparity (live‐bearing) has occurred independently in many animal lineages, but there are few phenotypic intermediates. The lizard Saiphos equalis exhibits bimodal reproduction, with some viviparous populations, and other oviparous populations with long egg‐retention, a rare trait where most of embryonic development occurs inside the mother prior to late ovipositioning. We posit that oviparous S. equalis represent an intermediate form between “true” oviparity and viviparity. We used transcriptomics to compare uterine gene expression in these two phenotypes, and provide a molecular model for the genetic control and evolution of reproductive mode. Many genes are differentially expressed throughout the reproductive cycle of both phenotypes, which have clearly different gene expression profiles overall. The differentially expressed genes within oviparous and viviparous individuals have broadly similar biological functions putatively important for sustaining embryos, including uterine remodelling, respiratory gas and water exchange, and immune regulation. These functional similarities indicate either that long egg‐retention is an exaptation for viviparity, or might reflect parallel evolution of similar gravidity‐related changes in gene expression in long egg‐retention oviparity. In contrast, gene expression changes across the reproductive cycle of long egg‐retaining oviparous S. equalis are dramatically different from those of “true” oviparous skinks (such as Lampropholis guichenoti ), supporting our assertion that oviparous S. equalis exhibit an intermediate phenotype between “true” oviparity and viviparity.

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Designing Monitoring Programs for Marine Protected Areas Within an Evidence Based Decision Making Paradigm - Keith R. Hayes; Geoffrey R. Hosack; Emma Lawrence; Paul Hedge; Neville S. Barrett; Rachel Przeslawski; M. Julian Caley; Scott D. Foster (Frontiers in Marine Science, 2019)

Using indices of atmospheric circulation to refine southern Australian winter rainfall climate projections - Michael R. Grose; Scott Foster; James S. Risbey; Stacey Osbrough; Louise Wilson (Climate Dynamics, 2019)

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

Understanding geographic variations of indoor radon potential for comprehensive cancer control planning - Michael Shayne Gallaway; Andrew S. Berens; Mary C. Puckett; Stephanie Foster (Cancer Causes & Control, 2019)

A review of the diets and feeding behaviours of a family of biologically diverse marine fishes (Family Syngnathidae) - C. G. Manning; S. J. Foster; A. C. J. Vincent (Reviews in Fish Biology and Fisheries, 2019)

Trends and indicators for quantifying moth abundance and occupancy in Scotland - E. B. Dennis; T. M. Brereton; B. J. T. Morgan; R. Fox; C. R. Shortall; T. Prescott; S. Foster (Journal of Insect Conservation, 2019)

The effects of trehalose glycolipid presentation on cytokine production by GM-CSF macrophages - Bridget L. Stocker; Kristel Kodar; Kanu Wahi; Amy J. Foster; Jacquie L. Harper; Daiki Mori; Sho Yamasaki; Mattie S. M. Timmer (Glycoconjugate Journal, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Changes in the trade of bycatch species corresponding to CITES regulations: the case of dried seahorse trade in Thailand - T.-C. Kuo; P. Laksanawimol; L. Aylesworth; S. J. Foster; A. C. J. Vincent (Biodiversity and Conservation, 2018)

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

A pilot study of prostate cancer knowledge among African American men and their health care advocates: implications for screening decisions - JoAnn S. Oliver; Rebecca S. Allen; Morgan K. Eichorst; Lisa Mieskowski; Patrick J. Ewell; Pamela Payne-Foster; Camille Ragin (Cancer Causes & Control, 2018)

Investigating the Complex Association Between Viral Ecology, Environment, and Northeast Pacific Sea Star Wasting - Ian Hewson; Kalia S. I. Bistolas; Eva M. Quijano Cardé; Jason B. Button; Parker J. Foster; Jacob M. Flanzenbaum; Jan Kocian; Chaunte K. Lewis (Frontiers in Marine Science, 2018)

Loss of the nutrient sensor TAS1R3 leads to reduced bone resorption - Michael S. Eaton; Nicholas Weinstein; Jordan B. Newby; Maggie M. Plattes; Hanna E. Foster; Jon W. Arthur; Taylor D. Ward; Stephen R. Shively; Ryann Shor; Justin Nathan; Hannah M. Davis; Lilian I. Plotkin; et al. (Journal of Physiology and Biochemistry, 2018)

A year in the life of a thrombolite: comparative metatranscriptomics reveals dynamic metabolic changes over diel and seasonal cycles - Artemis S. Louyakis; Hadrien Gourlé; Giorgio Casaburi; Rachelle M. E. Bonjawo; Alexandrea A. Duscher; Jamie S. Foster (Environmental Microbiology, 2018)
Summary Microbialites are one of the oldest known ecosystems on Earth and the coordinated metabolisms and activities of these mineral‐depositing communities have had a profound impact on the habitability of the planet. Despite efforts to understand the diversity and metabolic potential of these systems, there has not been a systematic molecular analysis of the transcriptional changes that occur within a living microbialite over time. In this study, we generated metatranscriptomic libraries from actively growing thrombolites, a type of microbialite, throughout diel and seasonal cycles and observed dynamic shifts in the population and metabolic transcriptional activity. The most transcribed genes in all seasons were associated with photosynthesis, but only transcripts associated with photosystem II exhibited diel cycling. Photosystem I transcripts were constitutively expressed at all time points including midnight and sunrise. Transcripts associated with nitrogen fixation, methanogenesis and dissimilatory sulfate reduction exhibited diel cycling, and variability between seasons. Networking analysis of the metatranscriptomes showed correlated expression patterns helping to elucidate how metabolic interactions are coordinated within the thrombolite community. These findings have identified distinctive temporal patterns within the thrombolites and will serve an important foundation to understand the mechanisms by which these communities form and respond to changes in their environment.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Simulations of a Cold-Air Pool in Utah’s Salt Lake Valley: Sensitivity to Land Use and Snow Cover - Christopher S. Foster; Erik T. Crosman; John D. Horel (Boundary-Layer Meteorology, 2017)

Spatial and temporal variation of diverse inter‐tidal algal assemblages in Southwest O‘ahu - Traci Erin Cox; Heather L. Spalding; Michael S. Foster (Marine Ecology, 2017)
Spatial and temporal variation in tropical inter‐tidal communities is poorly known, making predictions about the effects of climate change and other anthropogenic disturbances difficult. Along Southwest O‘ahu, Hawai'i, local residents are concerned about the environmental effects of coastal development and the perceived loss of targeted algal species, which are collected for human consumption. To describe the coastal benthic community and better understand the processes that form and maintain it, the abundance and composition of macroalgae were sampled in the region's inter‐tidal zone from 2006 to 2015. Sixty‐six macroalgal species and two broad algal assemblages were identified that corresponded to substrate topography and sand influence at a similar tidal elevation. Along flat carbonate benches with a sand beach, Phaeophyceae and Rhodophytes occurred in almost equal proportions, while shores with slightly more topographic relief and angular substrate were dominated by Rhodophytes. Foliose or turf algal forms were most common. Surveys captured the local invasion of an alga, Avrainvillea sp. and significant declines in abundant macroalgae in 2015 after a period of unseasonably warm, calm water. Temporal changes in algal assemblages were related to maximum water temperature and wave height but not precipitation. Thus, algal assemblages appear to be structured by local beach morphology as they interact with sand and wave activity and episodically by unusual weather events. However, manipulation and continuous monitoring of the algal assemblages coupled to sensing of the localized environment is necessary to confirm factors related to assembly maintenance and recent species shifts.

The role of glycerol in the pathogenic lifestyle of the rice blast fungus Magnaporthe oryzae - Andrew J. Foster; Lauren S. Ryder; Michael J. Kershaw; Nicholas J. Talbot (Environmental Microbiology, 2017)
Summary The rice blast fungus Magnaporthe oryzae elaborates a specialized cell called an appressorium, which is used to breach the tough outer cuticle of a rice leaf, enabling the fungus entry to host plant cells. The appressorium generates enormous turgor by accumulating glycerol to very high concentrations within the cell. Glycerol accumulation and melanization of the appressorium cell wall collectively drive turgor‐mediated penetration of the rice leaf. In this review, we discuss the potential metabolic sources of glycerol in the rice blast fungus and how appressorium turgor is focused as physical force at the base of the infection cell, leading to the formation of a rigid penetration peg. We review recent studies of M. oryzae and other relevant appressorium‐forming fungi which shed light on how glycerol is synthesized and how appressorium turgor is regulated. Finally, we provide some questions to guide avenues of future research that will be important in fully understanding the role of glycerol in rice blast disease.

MicroRNAs as therapeutics for future drug delivery systems in treatment of lung diseases - Kamal Dua; Nicole G. Hansbro; Paul S. Foster; Philip M. Hansbro (Drug Delivery and Translational Research, 2017)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Functional analysis of Agaricus bisporus serine proteinase 1 reveals roles in utilization of humic rich substrates and adaptation to the leaf‐litter ecological niche - Mary N. Heneghan; Claire Burns; Ana M. S. B. Costa; Kerry S. Burton; Michael P. Challen; Andy M. Bailey; Gary D. Foster (Environmental Microbiology, 2016)
Summary Agaricus bisporus is a secondary decomposer fungus and an excellent model for the adaptation, persistence and growth of fungi in humic‐rich environments such as soils of temperate woodland and pastures. The A. bisporus serine proteinase SPR1 is induced by humic acids and is highly expressed during growth on compost. Three Spr1 gene silencing cassettes were constructed around sense, antisense and non‐translatable‐stop strategies (pGRsensehph, pGRantihph and pGRstophph). Transformation of A. bisporus with these cassettes generated cultures showing a reduction in extracellular proteinase activity as demonstrated by the reduction, or abolition, of a clearing zone on plate‐based bioassays. These lines were then assessed by detailed enzyme assay, RT‐qPCR and fruiting. Serine proteinase activity in liquid cultures was reduced in 83% of transformants. RT‐qPCR showed reduced Spr1 mRNA levels in all transformants analysed, and these correlated with reduced enzyme activity. When fruiting was induced, highly‐silenced transformant AS5 failed to colonize the compost, whilst for those that did colonize the compost, 60% gave a reduction in mushroom yield. Transcriptional, biochemical and developmental observations, demonstrate that SPR1 has an important role in nutrient acquisition in compost and that SPR1 is a key enzyme in the adaptation of Agaricus to the humic‐rich ecological niche formed during biomass degradation.

Measuring success of a reintroduced population of the American burying beetle (Nicrophorus americanus Olivier) to Nantucket Island, MA - Andrew Mckenna-Foster; Lou Perrotti; Julia Blyth; Eric LoPresti; Robert S. Kennedy (Journal of Insect Conservation, 2016)

Spectrum of DNA variants for non-syndromic deafness in a large cohort from multiple continents - Denise Yan; Demet Tekin; Guney Bademci; Joseph Foster; F. Basak Cengiz; Abhiraami Kannan-Sundhari; Shengru Guo; Rahul Mittal; Bing Zou; Mhamed Grati; Rosemary I. Kabahuma; Mohan Kameswaran; et al. (Human Genetics, 2016)

Characterization of the stromatolite microbiome from L ittle D arby I sland, T he B ahamas using predictive and whole shotgun metagenomic analysis - Giorgio Casaburi; Alexandrea A. Duscher; R. Pamela Reid; Jamie S. Foster (Environmental Microbiology, 2016)
Summary Modern stromatolites represent ideal ecosystems to understand the biological processes required for the precipitation of carbonate due to their long evolutionary history and occurrence in a wide range of habitats. However, most of the prior molecular work on stromatolites has focused on understanding the taxonomic complexity and not fully elucidating the functional capabilities of these systems. Here, we begin to characterize the microbiome associated with stromatolites of L ittle D arby I sland, T he B ahamas using predictive metagenomics of the 16S r RNA gene coupled with direct whole shotgun sequencing. The metagenomic analysis of the Little Darby stromatolites revealed many shared taxa and core pathways associated with biologically induced carbonate precipitation, suggesting functional convergence within Bahamian stromatolites. A comparison of the L ittle D arby stromatolites with other lithifying microbial ecosystems also revealed that although factors, such as geographic location and salinity, do drive some differences within the population, there are extensive similarities within the microbial populations. These results suggest that for stromatolite formation, ‘who’ is in the community is not as critical as metabolic activities and environmental interactions. Together, these analyses help improve our understanding of the similarities among lithifying ecosystems and provide an important first step in characterizing the shared microbiome of modern stromatolites.

Integrating theory into disturbance interaction experiments to better inform ecosystem management - Claire N. Foster; Chloe F. Sato; David B. Lindenmayer; Philip S. Barton (Global Change Biology, 2016)
Managing multiple, interacting disturbances is a key challenge to biodiversity conservation, and one that will only increase as global change drivers continue to alter disturbance regimes. Theoretical studies have highlighted the importance of a mechanistic understanding of stressor interactions for improving the prediction and management of interactive effects. However, many conservation studies are not designed or interpreted in the context of theory and instead focus on case‐specific management questions. This is a problem as it means that few studies test the relationships highlighted in theoretical models as being important for ecological management. We explore the extent of this problem among studies of interacting disturbances by reviewing recent experimental studies of the interaction between fire and grazing in terrestrial ecosystems. Interactions between fire and grazing can occur via a number of pathways; one disturbance can modify the other's likelihood, intensity or spatial distribution, or one disturbance can alter the other's impacts on individual organisms. The strength of such interactions will vary depending on disturbance attributes (e.g. size or intensity), and this variation is likely to be nonlinear. We show that few experiments testing fire–grazing interactions are able to identify the mechanistic pathway driving an observed interaction, and most are unable to detect nonlinear effects. We demonstrate how these limitations compromise the ability of experimental studies to effectively inform ecological management. We propose a series of adjustments to the design of disturbance interaction experiments that would enable tests of key theoretical pathways and provide the deeper ecological understanding necessary for effective management. Such considerations are relevant to studies of a broad range of ecological interactions and are critical to informing the management of disturbance regimes in the context of accelerating global change.

Interactive effects of fire and large herbivores on web-building spiders - C. N. Foster; P. S. Barton; J. T. Wood; D. B. Lindenmayer (Oecologia, 2015)

The paleoclimatic and geochronologic utility of coring red beds and evaporites: a case study from the RKB core (Permian, Kansas, USA) - Gerilyn S. Soreghan; Kathleen C. Benison; Tyler M. Foster; Jay Zambito; Michael J. Soreghan (International Journal of Earth Sciences, 2015)
Drill core is critical for robust and high-resolution reconstructions of Earth’s climate record, as well demonstrated from both marine successions and modern long-lived lake systems. Deep-time climate reconstructions increasingly require core-based data, but some facies, notably red beds and evaporites, have garnered less attention for both paleoclimatic and geochronologic analyses. Here, we highlight studies from the Rebecca K. Bounds (RKB) core, a nearly continuous, >1.6 km drill core extending from the Cretaceous to the Mississippian, recovered from the US Midcontinent by Amoco Production Company in 1988, and serendipitously made available for academic research. Recent research conducted on this core illustrates the potential to recover high-resolution data for geochronologic and climatic reconstructions from both the fine-grained red bed strata, which largely represent paleo-loess deposits, and associated evaporite strata. In this case, availability of core was instrumental for (1) accessing a continuous vertical section that establishes unambiguous superposition key to both magnetostratigraphic and paleoclimatic analyses, and (2) providing pristine sample material from friable, soluble, and/or lithofacies and mineralogical species otherwise poorly preserved in surface exposures. The potential for high-resolution paleoclimatic reconstruction from coring of deep-time loess strata in particular remains severely underutilized.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Delineating optimal settlement areas of juvenile reef fish in Ngederrak Reef, Koror state, Republic of Palau - Victor S. Ticzon; Greg Foster; Laura T. David; Peter J. Mumby; Badi R. Samaniego; Val Randolf Madrid (Environmental Monitoring and Assessment, 2015)

Contrast-enhanced molecular ultrasound differentiates endoglin genotypes in mouse embryos - J. M. Denbeigh; B. A. Nixon; J. J. Y. Lee; M. Jerkic; P. A. Marsden; M. Letarte; M. C. Puri; F. S. Foster (Angiogenesis, 2015)

Novel life‐history data for threatened seahorses provide insight into fishery effects - J. M. Lawson; S. J. Foster; A. C. O. Lim; V. C. Chong; A. C. J. Vincent (Journal of Fish Biology, 2015)
Life‐history variables for three incidentally captured species of seahorse (Kellogg's seahorse Hippocampus kelloggi , the hedgehog seahorse Hippocampus spinosissimus and the three‐spot seahorse Hippocampus trimaculatus ) were established using specimens obtained from 33 fisheries landing sites in Peninsular Malaysia. When samples were pooled by species across the peninsula, sex ratios were not significantly different from unity, and height and mass relationships were significant for all species. For two of these species, height at physical maturity ( H M ) was smaller than the height at which reproductive activity ( H R ) commenced: H. spinosissimus ( H M = 99·6 mm, H R = 123·2 mm) and H. trimaculatus ( H M = 90·5 mm, H R = 121·8 mm). For H. kelloggi , H M could not be estimated as all individuals were physically mature, while H R = 167·4 mm. It appears that all three Hippocampus spp. were, on average, caught before reproducing; height at 50% capture ( H C ) was ≥ H M but ≤ H R . The results from this study probe the effectiveness of assessment techniques for data‐poor fisheries that rely heavily on estimates of length at maturity, especially if maturity is poorly defined. Findings also question the sustainability of H. trimaculatus catches in the south‐west region of Peninsular Malaysia, where landed specimens had a notably smaller mean height (86·2 mm) and markedly skewed sex ratio (6% males) compared with samples from the south‐east and north‐west of the peninsula.

Reducing the volume of sprint interval training does not diminish maximal and submaximal performance gains in healthy men - Jason G. E. Zelt; Paul B. Hankinson; William S. Foster; Cameron B. Williams; Julia Reynolds; Ellen Garneys; Michael E. Tschakovsky; Brendon J. Gurd (European Journal of Applied Physiology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Anti-VEGF therapy reduces intestinal inflammation in Endoglin heterozygous mice subjected to experimental colitis - Daniela S. Ardelean; Melissa Yin; Mirjana Jerkic; Madonna Peter; Bo Ngan; Robert S. Kerbel; F. Stuart Foster; Michelle Letarte (Angiogenesis, 2014)

Do communities exist? Complex patterns of overlapping marine species distributions - Rebecca Leaper; Piers K. Dunstan; Scott D. Foster; Neville S. Barrett; Graham J. Edgar (Ecology, 2014)
Understanding the way in which species are associated in communities is a fundamental question in ecology. Yet there remains a tension between communities as highly structured units or as coincidental collections of individualistic species. We explored these ideas using a new statistical approach that clusters species based on their environmental response: a species archetype, rather than clustering sites based on their species composition. We found groups of species that are consistently highly correlated, but that these groups are not unique to any set of locations and overlap spatially. The species present at a single site are a realization of species from the (multiple) archetype groups that are likely to be present at that location based on their response to the environment.

Selection of low-variance expressed Malus x domestica (apple) genes for use as quantitative PCR reference genes (housekeepers) - Judith Bowen; Hilary S. Ireland; Ross Crowhurst; Zhiwei Luo; Amy E. Watson; Toshi Foster; Nigel Gapper; Jim J. Giovanonni; James P. Mattheis; Chris Watkins; David Rudell; Jason W. Johnston; et al. (Tree Genetics & Genomes, 2014)

Endoglin and activin receptor-like kinase 1 heterozygous mice have a distinct pulmonary and hepatic angiogenic profile and response to anti-VEGF treatment - Daniela S. Ardelean; Mirjana Jerkic; Melissa Yin; Madonna Peter; Bo Ngan; Robert S. Kerbel; F. Stuart Foster; Michelle Letarte (Angiogenesis, 2014)

Metabolic potential of lithifying cyanobacteria-dominated thrombolitic mats - Jennifer M. Mobberley; Christina L. M. Khodadad; Jamie S. Foster (Photosynthesis Research, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Reproductive success in a natural population of male three‐spined stickleback Gasterosteus aculeatus : effects of nuptial colour, parasites and body size - T. C. Sparkes; V. Rush; D. A. Kopp; S. A. Foster (Journal of Fish Biology, 2013)
The effects of nuptial colour, parasites and body size on reproductive success were examined in a natural population of three‐spined stickleback Gasterosteus aculeatus . Reproductive males were collected, with the contents of their nests, during the embryo‐guarding stage from Lynne Lake (Cook Inlet, Alaska, U.S.A.), and nuptial colour, infection status and body size were recorded. Regression analysis revealed that male body size was the only predictor, of those measured, of reproductive success in nature.

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Glaciotectonic deformation associated with the Orient Point–Fishers Island moraine, westernmost Block Island Sound: further evidence of readvance of the Laurentide ice sheet - Lawrence J. Poppe; Robert N. Oldale; David S. Foster; Shepard M. Smith (Geo-Marine Letters, 2012)

Factors affecting mosquito populations in created wetlands in urban landscapes - Priyanka Yadav; Woodbridge A. Foster; William J. Mitsch; Parwinder S. Grewal (Urban Ecosystems, 2012)

Submarine pyroclastic deposits formed during the 20th May 2006 dome collapse of the Soufrière Hills Volcano, Montserrat - J. Trofimovs; C. Foster; R. S. J. Sparks; S. Loughlin; A. Le Friant; C. Deplus; L. Porritt; T. Christopher; R. Luckett; P. J. Talling; M. R. Palmer; T. Le Bas (Bulletin of Volcanology, 2012)

Comparative microbial diversity analyses of modern marine thrombolitic mats by barcoded pyrosequencing - Jennifer M. Mobberley; Maya C. Ortega; Jamie S. Foster (Environmental Microbiology, 2012)
Summary Thrombolites are unlaminated carbonate structures that form as a result of the metabolic interactions of complex microbial mat communities. Thrombolites have a long geological history; however, little is known regarding the microbes associated with modern structures. In this study, we use a barcoded 16S rRNA gene‐pyrosequencing approach coupled with morphological analysis to assess the bacterial, cyanobacterial and archaeal diversity associated with actively forming thrombolites found in Highborne Cay, Bahamas. Analyses revealed four distinct microbial mat communities referred to as black, beige, pink and button mats on the surfaces of the thrombolites. At a coarse phylogenetic resolution, the domain bacterial sequence libraries from the four mats were similar, with Proteobacteria and Cyanobacteria being the most abundant. At the finer resolution of the rRNA gene sequences, significant differences in community structure were observed, with dramatically different cyanobacterial communities. Of the four mat types, the button mats contained the highest diversity of Cyanobacteria , and were dominated by two sequence clusters with high similarity to the genus Dichothrix, an organism associated with the deposition of carbonate. Archaeal diversity was low, but varied in all mat types, and the archaeal community was predominately composed of members of the Thaumarchaeota and Euryarchaeota . The morphological and genetic data support the hypothesis that the four mat types are distinctive thrombolitic mat communities.

Detecting end-member structural and biological elements of a coral reef using a single-beam acoustic ground discrimination system - Greg Foster; Victor S. Ticzon; Bernhard M. Riegl; Peter J. Mumby (International Journal of Remote Sensing, 2011)

Mechanisms of HIV-1 Nef Function and Intracellular Signaling - John L. Foster; Sarah J. Denial; Brenda R. S. Temple; J. Victor Garcia (Journal of Neuroimmune Pharmacology, 2011)

Conservation and management of seahorses and other Syngnathidae - A. C. J. Vincent; S. J. Foster; H. J. Koldewey (Journal of Fish Biology, 2011)
This article analyses the pressures on seahorses and explores conservation responses. It focuses on seahorses ( Hippocampus spp.) but also considers pipefishes and seadragons, especially where they can fill gaps in seahorse knowledge. The charisma of many syngnathids can make them good flagship species for threats and solutions in marine conservation. The article combines a synthesis of published literature with new data on the trade in seahorses for traditional medicine, aquarium display and curiosities. Most traded seahorses come from trawl by‐catch, although seahorses are also targeted. The total extraction is large, tens of millions of animals annually, and unsustainable. A first review of the effect of habitat change on syngnathids raises many questions, while suggesting that some species may cope better than others. The combination of pressures means that many species of syngnathid are now included in the IUCN Red List of Threatened Species or national equivalents. In addition, seahorse exports from 175 countries are limited to sustainable levels under the Convention on International Trade in Endangered Species (CITES) of Wild Fauna and Flora. Possible conservation measures include marine protected areas, fisheries management, select aquaculture ventures, trade regulation, improved governance (particularly) and consumer engagement.

The potential for paleolimnology to determine historic sediment delivery to rivers - I. D. L. Foster; A. L. Collins; P. S. Naden; D. A. Sear; J. I. Jones; Y. Zhang (Journal of Paleolimnology, 2011)

Pathology: coming in from the cold - Christopher S. Foster (Cell and Tissue Banking, 2011)

Using life‐history information to assess potential effects of shrimp trawling on small fishes - S. J. Foster; A. C. J. Vincent (Journal of Fish Biology, 2010)
The current study presents information on size distributions, size at recruitment to the fishery, size at maturity and patterns of reproduction for several small benthic fishes caught as by‐catch in the southern Gulf of California (Mexico) shrimp trawl fishery: sand perch Diplectrum spp., lumptail searobin Prionotus stephanophrys , bigscale goatfish Pseudupeneus grandisquamis and silver stardrum Stellifer illecebrosus . Pseudupeneus grandisquamis , P. stephanophrys and S. illecebrosus populations were all sexually dimorphic in size. Total‐length ( L T )‐based analyses did not provide reliable information on survival and growth. The majority of sampled P. grandisquamis and S. illecebrosus were caught before reproductive maturity, whereas the majority of Diplectrum spp. and almost all P. stephanophrys were mature when caught. L T at 50% gear retention ( L Tc , mm) v . 50% maturity ( L Tm , mm): Diplectrum spp. 124·53 v . 131·43; P. grandisquamis 90·98 v . 135·20; S. illecebrosus 82·55 v . 137·30. L Tc for P. stephanophrys was 104·73, but L Tm could not be modelled for this species as almost all captured individuals were mature. Diplectrum spp., P. grandisquamis and S. illecebrosus were indeterminate spawners, whereas P. stephanophrys appeared to be a determinate spawner. Sex ratios were equal for each of the gonochoristic species. In general, the gonado‐somatic index ( I G ) increased with increasing L T for all except P. stephanophrys , where I G decreased with increasing L T for both males and females. Mature individuals of all taxa were found throughout the sampling period (September to March), and I G increased with sample day for all except females of P. grandisquamis . The current data suggest the potential for fishery effects on sampled populations of P. grandisquamis and S. illecebrosus .

Improving groundwater resource accounting in irrigated areas : a prerequisite for promoting sustainable use - S. S. D. Foster; C. J. Perry (Hydrogeology Journal, 2010)

Damage to the reefs of Port Honduras Marine Reserve, Belize, during the 28 May 2009 earthquake - N. L. Foster; M. Williams; S. Chan; C. Ramirez; V. Vasquez (Coral Reefs, 2010)

The white-chinned petrel (Procellaria aequinoctialis) on South Georgia: population size, distribution and global significance - A. R. Martin; S. Poncet; C. Barbraud; E. Foster; P. Fretwell; P. Rothery (Polar Biology, 2009)

Resistance to race 2 and cross-resistance to race 1 of Kabatiella caulivora in Trifolium subterraneum and T. purpureum - Hua Li; P. G. H. Nichols; S. Han; K. J. Foster; K. Sivasithamparam; M. J. Barbetti (Australasian Plant Pathology, 2009)

Essential oil production: relationship with abundance of glandular trichomes in aerial surface of plants - Kamal K. Biswas; Adam J. Foster; Theingi Aung; Soheil S. Mahmoud (Acta Physiologiae Plantarum, 2009)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Development of SHRIMP - T. R. Ireland*; S. Clement; W. Compston; J. J. Foster; P. Holden; B. Jenkins; P. Lanc; N. Schram; I. S. Williams (Australian Journal of Earth Sciences, 2008)

Using multiple archives to understand past and present climate–human–environment interactions: the lake Erhai catchment, Yunnan Province, China - J. A. Dearing; R. T. Jones; J. Shen; X. Yang; J. F. Boyle; G. C. Foster; D. S. Crook; M. J. D. Elvin (Journal of Paleolimnology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Synthesis and pharmacological evaluation of m-terphenyl amines as cyclooxygenase inhibitors - John D. Bauer; Michael S. Foster; Jeffrey D. Hugdahl; Kristi L. Burns; Sheldon W. May; Stanley H. Pollock; Horace G. Cutler; Stephen J. Cutler (Medicinal Chemistry Research, 2007)

Nitrogen fixation by unicellular diazotrophic cyanobacteria in the temperate oligotrophic North Pacific Ocean - Joseph A. Needoba; Rachel A. Foster; Carole Sakamoto; Jonathan P. Zehr; Kenneth S. Johnson (Limnology and Oceanography, 2007)
N 2 fixation has been understudied in marine environments outside of the subtropical and tropical oceans and where water temperatures are typically below 20‐25°C. We identified nifH phylotypes and measured N 2 fixation rates under ambient conditions (maximum of 19°C) in water collected 750 km off the coast of California in oligotrophic waters of the North Pacific Ocean (34°N, 129°W). Near‐surface N 2 fixation rates averaged 0.25 ± 0.05 nmol N L −1 d −1 for 24 incubation bottles. Despite low ambient concentrations of iron ( −1 ) and phosphorus ( −1 ), N 2 fixation rates were unaffected by iron and phosphorus amendments. Using reverse transcription‐quantitative polymerase chain reaction (RT‐QPCR) methodology, we estimated transcript abundance and patterns of expression for several unicellular diazotrophs, including the group A phylotype, which showed the highest daily mRNA abundances. The N 2 ‐fixing assemblage extended to 60‐80 m depth, well below the seasonal thermocline (40 m). The calculated areal N 2 fixation rate (15 µmol N m −2 d −1 ) was small compared with estimates from other regions of the Pacific; however, the estimated fixation rate was similar to other published results, suggesting that processes other than cellular growth rate may determine the abundance of unicellular diazotrophs. Despite the low N 2 fixation rates, the new nitrogen added to the euphotic zone by N 2 fixation could account for at least 10% of new production during the study period.

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

Growth-phase dependent differential gene expression in Synechocystis sp. strain PCC 6803 and regulation by a group 2 sigma factor - Jamie S. Foster; Abhay K. Singh; Lynn J. Rothschild; Louis A. Sherman (Archives of Microbiology, 2007)

Incorporation of Plant Residues into Soil Organic Matter Fractions With Grassland Management Practices in the North American Midwest - S. A. Billings; C. M. Brewer; B. L. Foster (Ecosystems, 2006)

The Definition of British Water Beetle Species Pools (Coleoptera) and their Relationship to Altitude, Temperature, Precipitation and Land Cover Variables - M. D. Eyre; G. N. Foster; M. L. Luff; S. P. Rushton (Hydrobiologia, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Modelling the spread of scrapie in a sheep flock: evidence for increased transmission during lambing seasons - S. Touzeau; M. E. Chase-Topping; L. Matthews; D. Lajous; F. Eychenne; N. Hunter; J. D. Foster; G. Simm; J.-M. Elsen; M. E. J. Woolhouse (Archives of Virology, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Character and distribution of exposed glaciodeltaic deposits off outer Cape Cod, Massachusetts, and their effects on hydrogeology and benthic habitats - L. J. Poppe; D. S. Foster; W. W. Danforth (Geo-Marine Letters, 2006)

Use of optical density as a measure of Claviceps africana conidial suspension concentration - D. J. Herde; M. J. Ryley; S. D. Foster; V. J. Galea; R. G. Henzell; D. R. Jordan (Australasian Plant Pathology, 2006)

Carbon monoxide levels at a toll plaza near Durban, South Africa - R. D. Diab; S. J. Foster; K. François; B. S. Martincigh; L. F. Salter (Environmental Chemistry Letters, 2005)

Enhancing Sustainability of the International Trade in Seahorses with a Single Minimum Size Limit - S. J. FOSTER; A. C. J. VINCENT (Conservation Biology, 2005)
Management tools are needed to help regulate the international trade in seahorses ( Hippocampus spp.) under the Convention on International Trade in Endangered Species (CITES) of Wild Fauna and Flora. Given the limited understanding of seahorse population dynamics and fishing mortality, a single minimum size limit for all seahorse species appears to be a useful initial step toward adaptive management, both biologically and socially. We collected data on maximum height and size at first maturity for 32 seahorse species and cross‐validated the data with results from an analysis across marine teleosts. A minimum height restriction of 10 cm would permit, based on calculated data, reproduction in 15 species before they recruited to the fishery. Of the remaining 17 species, 16 were essentially not in international trade, were safeguarded under domestic legislation, or were partly protected by this size limit. Only one species, H. kelloggi , was not well served by the 10‐cm minimum size limit. The CITES technical committee on animals has now decided to propose this single size limit to all 167 signatory nations as one option toward sustainable trade. Complementary management measures for seahorses are also required, particularly for populations primarily exploited in bycatch.

Enhancing Sustainability of the International Trade in Seahorses with a Single Minimum Size Limit - S. J. FOSTER; A. C. J. VINCENT (Conservation Biology, 2005)

Impedance-gradient electrode reduces skin irritation induced by transthoracic defibrillation - P. F. Meyer; P. D. Gadsby; D. Van Sickle; W. E. Schoenlein; K. S. Foster; G. P. Graber (Medical & Biological Engineering & Computing, 2005)

Comparative Aquatic Toxicity Evaluation of 2-(Thiocyanomethylthio)benzothiazole and Selected Degradation Products Using Ceriodaphnia dubia - S. T. Nawrocki; K. D. Drake; C. F. Watson; G. D. Foster; K. J. Maier (Archives of Environmental Contamination and Toxicology, 2005)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

Comparing the effects of farming practices on ground beetle (Coleoptera: Carabidae) and spider (Araneae) assemblages of Scottish farmland - Lorna J. Cole; David I. McCracken; Iain S. Downie; Peter Dennis; Garth N. Foster; Tony Waterhouse; Kevin J. Murphy; Anna L. Griffin; Mike P. Kennedy (Biodiversity and Conservation, 2005)

The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; S. K. Zavriev; C. M. Fauquet (Archives of Virology, 2004)

U-Pb columbite-tantalite chronology of rare-element pegmatites using TIMS and Laser Ablation-Multi Collector-ICP-MS - S. R. Smith; G. L. Foster; R. L. Romer; A. G. Tindle; S. P. Kelley; S. R. Noble; M. Horstwood; F. W. Breaks (Contributions to Mineralogy and Petrology, 2004)

Life history and ecology of seahorses: implications for conservation and management - S. J. Foster; A. C. J. Vincent (Journal of Fish Biology, 2004)
We present the first synthesis of the life history and ecology of seahorses, compare relationships for seahorses with other marine teleosts and identify research needs. Seahorses occurred primarily amidst temperate seagrasses and tropical coral reefs. Population densities were generally low, ranging from 0 to 0·51 individuals m −2 , but reached 10 m −2 in some patches. Inferred life spans ranged from 1 to 5 years. Seahorses consumed live prey and possibly changed diet as they grew. Growth rates are poorly investigated to date. Reproduction and mating systems are the best‐studied aspects of seahorse ecology. The relationship between size at first maturity and maximum size in seahorses conformed to that for other marine teleosts. All seahorse species were monogamous within a cycle, but some were polygamous across cycles. Direct transfer of clutches to the brood pouch of the male fish made it difficult to measure clutch size in live seahorses. After brooding, males released from c . 5 to 2000 young, depending on species and adult size. Newborn young measured from 2 to 20 mm in length, which was a narrower size range than the 17‐fold difference that occurred in adult size. Newborn body size had no relationship to adult size. Both eggs and young were larger than expected among marine teleosts, even when considering only those with parental care, but brood size at release was lower than expected, perhaps because the young were more developed. The size of adults, eggs and young increased with increasing latitude, although brood size did not. Considerable research is needed to advance seahorse conservation and management, including (a) fisheries‐dependent and fisheries‐independent abundance estimates, (b) age‐ or stage‐based natural and fishing mortalities, (c) growth rates and age at first maturity, and (d) intrinsic rates of increase and age‐ or size‐specific reproductive output. Current data confirm that seahorses are likely to be vulnerable to high levels of exploitation.

Downstream of downtown: urban wastewater as groundwater recharge - S. S. D. Foster; P. J. Chilton (Hydrogeology Journal, 2004)

Long-Term Soil Accumulation of Chromium, Copper, and Arsenic Adjacent to Preservative-Treated Wood - S. Lebow; D. Foster; J. Evans (Bulletin of Environmental Contamination and Toxicology, 2004)

Complete nucleotide sequence and analysis of pPSR1 (72,601 bp), a pPT23A-family plasmid from Pseudomonas syringae pv. syringae A2 - G. W. Sundin; C. T. Mayfield; Y. Zhao; T. S. Gunasekera; G. L. Foster; M. S. Ullrich (Molecular Genetics and Genomics, 2004)

Tachykinin substance P signaling involved in diesel exhaust-induced bronchopulmonary neurogenic inflammation in rats - Simon S. Wong; Nina N. Sun; Ingegerd Keith; Chol-Bum Kweon; David E. Foster; James J. Schauer; Mark L. Witten (Archives of Toxicology, 2003)

Comparison of partial sequence of the cap binding protein (eIF4E) isolated from Agaricus bisporus and its pathogen Verticillium fungicola - A.L. Athey-Pollard; M. Kirby; S. Potter; C. Stringer; P.R. Mills; G.D. Foster (Mycopathologia, 2003)

Increase in synthesis of human monoclonal antibodies by transfected Sp2/0 myeloma mouse cell line under conditions of microgravity - L.J.R. Foster; D. Catzel; S. Atwa; M. Zarka; S.M. Mahler (Biotechnology Letters, 2003)

Changing suspended sediment and particulate phosphorus loads and pathways in underdrained lowland agricultural catchments; Herefordshire and Worcestershire, U.K. - I. D. L. Foster; A. S. Chapman; R. M. Hodgkinson; A. R. Jones; J. A. Lees; S. E. Turner; M. Scott (Hydrobiologia, 2003)

Comparison of Human Duodenum and Caco-2 Gene Expression Profiles for 12,000 Gene Sequences Tags and Correlation with Permeability of 26 Drugs - Duxin Sun; Hans Lennernas; Lynda S. Welage; Jeffery L. Barnett; Christopher P. Landowski; David Foster; David Fleisher; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2002)

A constitutive gene expression system derived from the tCUP cryptic promoter elements - K. Malik; K. Wu; X.-Q. Li; T. Martin-Heller; M. Hu; E. Foster; L. Tian; C. Wang; K. Ward; M. Jordan; D. Brown; S. Gleddie; et al. (Theoretical and Applied Genetics, 2002)

Bioaccumulation of PCBs in Aquatic Biota from a Tidal Freshwater Marsh Ecosystem - B. S. Crimmins; P. Doelling Brown; D. P. Kelso; G. D. Foster (Archives of Environmental Contamination and Toxicology, 2002)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Plasma Androgen Correlation, EROD Induction, Reduced Condition Factor, and the Occurrence of Organochlorine Pollutants in Reproductively Immature White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster, M. S. Fitzpatrick, G. W. (Archives of Environmental Contamination and Toxicology, 2001)

Dynamic Modelling of Spatially Variable Catchment Hydrochemistry for Critical Loads Assessment - Helen J. Foster; Matthew J. Lees; Howard S. Wheater; Colin Neal; Brian Reynolds (Water, Air, & Soil Pollution, 2001)

Growth rate and potential climate record from a rhodolith using 14C accelerator mass spectrometry - Brian R. Frantz; Michaele Kashgarian; Kenneth H. Coale; Michael S. Foster (Limnology and Oceanography, 2000)
Rhodoliths, free‐living calcareous red algae, create large and diverse habitats worldwide. Although these plants are abundant and ecologically important, little is known about their growth rate. We determined the growth rate for an individual rhodolith, Lithothamnium crassiusculum , from the southern Gulf of California through 14 C analysis using accelerator mass spectrometry (AMS) to be 0.6 mm yr −1 . This growth rate suggests large L. crassiusculum , which have been found with radii in excess of 6 cm, may live over 100 yr. Declines in the Δ 14 C record associated with the large El Niño events of 1957, 1982, and 1992 indicate 14 C analysis may lead to identification of important climate events in the more distant past. The ability to determine changes in past ocean circulation related to changes in past climatic conditions through AMS 14 C analysis of rhodoliths would increase the geographic range of available climate records from the tropical oceans to the entire global ocean and potentially allow for the determination of past climate conditions from rhodoliths in fossil beds.

Identification of a Sex Pheromone Component of the Raspberry Budmoth, Heterocrossa rubophaga - S. P. Foster; W. P. Thomas (Journal of Chemical Ecology, 2000)

An Isolated In-Situ Rat Head Perfusion Model for Pharmacokinetic Studies - Kelley A. Foster; George D. Mellick; Michael Weiss; Michael S. Roberts (Pharmaceutical Research, 2000)

Chemical Stimuli from Apple Influence the Behavior of Neonate Caterpillars of the Generalist Herbivore, Epiphyas postvittana - M. O. Harris; M. Sandanayake; S. P. Foster (Journal of Chemical Ecology, 1999)

Analysis of a translational enhancer present within the 5′-terminal sequence of the genomic RNA of potato virus S - R. L. Turner; M. Glynn; S. C. Taylor; M.-K. Cheung; C. Spurr; D. Twell; G. D. Foster (Archives of Virology, 1999)

Tetrodotoxin suppresses morphological enhancement of the metastatic MAT-LyLu rat prostate cancer cell line - S. P. Fraser; Y. Ding; A. Liu; C. S. Foster; M. B. A. Djamgoz (Cell and Tissue Research, 1999)

Distribution of aquatic macroinvertebrates within peatland pool complexes in the Flow Country, Scotland - I. S. Downie; J. C. Coulson; G. N. Foster; D. P. Whitfield (Hydrobiologia, 1998)

Influence of Stimuli from Camellia japonica on Ovipositional Behavior of Generalist Herbivore Epiphyas postvittana - S. P. Foster; A. J. Howard (Journal of Chemical Ecology, 1998)

Glucose and memory: fractionation of enhancement effects? - J. K. Foster; P. G. Lidder; S. I. Sünram (Psychopharmacology, 1998)

Effects of gravidity on habitat use and antipredator behaviour in three‐spined sticklebacks - A. D. Rodewald; S. A. Foster† (Journal of Fish Biology, 1998)
Habitat use was examined in six Alaskan populations of three‐spined sticklebacks Gasterosteus aculeatus . In three lakes with predatory fishes, gravid female sticklebacks remained closer to refuge than did non‐gravid females, while those in lakes devoid of piscivores did not display this shift in behaviour. Gravid females in a lake with predatory rainbow trout Oncorhynchus mykiss used different evasive manoeuvres than did non‐gravid females during in situ encounters with a model rainbow trout. Gravid females were more likely to incorporate a protean element in their flight moffements than were non‐gravid females. Offerall, these data suggest that gravid female three‐spined sticklebacks modify habitat use and escape behaviour to reduce vulnerability to predators.

Impact of Human Activity on Regional Forest Composition and Dynamics in Central New England - Janice L. Fuller; David R. Foster; Jason S. McLachlan; Natalie Drake (Ecosystems, 1998)

A bymovirus PCR primer and partial nucleotide sequence provides further evidence for the recognition of rice necrosis mosaic virus as a bymovirus - J.L. Badge; S. Kashiwazaki; S. Lock; G.D. Foster (European Journal of Plant Pathology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Trends in Genetic and Environmental Parameters for Height, Diameter, and Volume in a Multilocation Clonal Study with Loblolly Pine - A. D. Paul; G. S. Foster; T. Caldwell; J. McRae (Forest Science, 1997)
Seedlings from 30 full-sib families (contained in 2, 4 x 4 factorials) of loblolly pine (Pinus taeda L.) were cloned and planted in three test sites in Georgia. Analyses were conducted on total height at ages 1 to 5 yr in the field, dbh at age 5, and individual tree volume at age 5. Four sources of genetic control were tested: male parent, female parent, male x female parent interaction, and clone within family. Differential growth responses due to test sites were present. Significant differences were detected among male parents for only one (age 5 height) of the seven traits in only one factorial. However, variation for height among female parents was found at ages 1 to 5 in only one of the two factorials accounting for 1% to 9% of the total variation. Significant effects of clone within family were found at all ages in one factorial and at ages 1, 3, and 4 in the other factorial for height but not for dbh or individual tree volume. None of the parental sources (male, female, or male x female) were interactive with test sites except one isolated case at age 2 in one factorial. However, the clone within family source of variation interacted significantly with site for height at ages 3 to 5 in factorial 1. Differences due to male or female parent effects were somewhat lower than has been found in other similar studies, possibly due to the relatively low number of parents in both factorials and hence, sampling effects. Future genetic studies should include more parents in the mating design but with approximately the same number of cloned individuals per cross in order to provide a better test of sources of variation. Trends in genetic and environmental variances and heritabilities were examined. Additive genetic variance (VA')for tree height displayed a steady increase from age 1 to 5. Dominance genetic variance (VD') for height also increased steadily over the same age range. The relationship between VA' and VD' differed between the two factorials. In factorial 1, VA' was larger than VD' for ages 1 to 4, then VD' became larger for age 5. The reverse pattern occurred in factorial 2. Epistatic genetic variance was detected only at age 1 for height in factorial 1 and at ages 1 and 3 in factorial 2. Dominance variance equaled or exceeded additive genetic variance for dbh and individual tree volume at age 5. Narrow-sense and broad-sense heritabilities for height were low to intermediate (0.05 to 0.37) from ages 1 to 5 and were more or less stable over ages. The importance of dominance genetic variance, at least to age 5, underscores the likelihood of additional genetic gains through a clonal tree improvement and deployment program beyond the gains achieved in a seed orchard/seedling based program. For. Sci. 42(1):87-98.

The mineralogy of the Golden Sunlight gold-silver telluride deposit, Whitehall, Montana, U.S.A. - P. G. Spry; F. Foster; J. S. Truckle; T. H. Chadwick (Mineralogy and Petrology, 1997)

A CaMV 35S promoter driven cDNA clone of tobacco mosaic virus can infect host plant tissue despite being uninfectious when manually inoculated onto leaves - E. M. Dagless; M. H. Shintaku; R. S. Nelson; G. D. Foster (Archives of Virology, 1997)

The effect of elevated intracranial pressure on the vibrational response of the ovine head - Milan Stevanovic; George R. Wodicka; Joe D. Bourland; George P. Graber; Kirk S. Foster; Gary C. Lantz; Willis A. Tacker; Allen Cymerman (Annals of Biomedical Engineering, 1995)

The biodegradation of poly-3-hydroxyalkanoates, PHAs, with long alkyl substitutents byPseudomonas maculicola - L. J. R. Foster; S. J. Zervas; R. W. Lenz; R. C. Fuller (Biodegradation, 1995)

Comparison of rectangular and exponential current pulses for evoking sensation - Jerry L. Wessale; Leslie A. Geddes; Gregory M. Ayers; Kirk S. Foster (Annals of Biomedical Engineering, 1992)

Myxoviruses do not induce non-specific alterations in membrane permeability early on in infection - K. A. Foster; K. J. Micklem; G. Agnarsdottir; C. L. Lancashire; N. N. Bogomolova; Y. S. Boriskin; C. A. Pasternak (Archives of Virology, 1983)

Cooperative behavior and social organization of the Swallow-tailed Manakin (Chiroxiphia caudata) - Mercedes S. Foster (Behavioral Ecology and Sociobiology, 1981)

Lethal germination of spores ofBacillus megaterium 9885 - R. S. Holdom; J. W. Foster (Antonie van Leeuwenhoek, 1967)

Sectional notes - C. L. Fitch; E. L. Newdick; Frank W. Hussey; Ralph W. Donaldson; J. R. Livermore; E. B. Lyman; Robert Schmidt; E. J. Taintor; E. B. Tussing; J. B. R. Dickey; K. W. Lauer; G. S. Ralston; et al. (American Journal of Potato Research, 1934)